Extended Versus Standard Complete Mesocolon Excision in Sigmoid Colon Cancer: A Multicenter Randomized Controlled Trial. Issue 2 (19th August 2021) - Planellas, Pere; Marinello, Franco; Elorza, Garazi; Golda, Thomas; Farrés, Ramon; Espín-Basany, Eloy; Enríquez-Navascués, Jose Mari; Kreisler, Esther; Cornejo, Lídia; Codina-Cazador, Antoni
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to evaluate whether extended complete mesocolic excision (e-CME) for sigmoid colon cancer improves oncological outcomes without compromising morbidity or functional results. Background: In surgery for cancer of the sigmoid colon and upper rectum, s-CME removes the lymphofatty tissue surrounding the inferior mesenteric artery (IMA), but not the lymphofatty tissue surrounding the portion of the inferior mesenteric vein that does not run parallel to the IMA. Evidence about the safety and efficacy of extending CME to include this tissue is lacking. Methods: This single-blind study randomized sigmoid cancer patients at 4 centers to undergo e-CME or s-CME. The primary outcome was the total number of lymph nodes harvested. Secondary outcomes included disease-free and overall survival at 2 years, morbidity, and bowel and genitourinary function. Clinicaltrials.gov: NCT03107650. Results: We analyzed 93 patients (46 e-CME and 47 s-CME). Perioperative outcomes were similar between groups. No differences between groups were found in the total number of lymph nodes harvested [21 (interquartile range, IQR, 14–29) in e-CME vs 20 (IQR, 15–27) in s-CME, P = 0.873], morbidity ( P = 0.829), disease-free survival ( P = 0.926), or overall survival ( P = 0.564). The extended specimen yielded a median of 1 lymph node (range, 0–6), none of which were positive. Bowel function recovery was similar between arms at all timepoints. Males undergoing e-CME had worse recovery of urinary function ( P = 0.026). Conclusion: Extending lymphadenectomy to include the IMV territory did not increase the number of lymph nodes or improve local recurrence or survival rates.